Nature is Relative: Religious Affiliation, Environmental Attitudes, and Political Constraints on the Pine Ridge Indian Reservation - Pickering, Kathleen Ann (Journal for the study of religion, nature and culture, 2008)
An industrial model of conservation defines nature as a relative space with minimal human impacts. For Native communities, such as the Lakota on the Pine Ridge Reservation in South Dakota, nature is part of an extended kinship system occupied by various relatives, both animate and inanimate, human and non-human. As a result, Lakota beliefs and values enhance positive environmental attitudes, but are embedded in religious perspectives rather than conservation of an abstracted nature. We conceptualize the interactions between individual ethics and actual conservation behavior as existing in three layers. At the grassroots layer, defined through individual and family relationships, spiritual ties to nature are generated through various Lakota philosophies, including equality across species. At the tribal or political layer, Lakota politicians often use Lakota ‘traditions’ strategically to reassert tribal sovereignty and control over natural resources and development policy, as well as to legitimize their quest for mainstream political spoils. At the structural layer of the federal government, individual beliefs are often violated by the dominant conservation paradigm, using scientific narratives and disembodied economic returns to replace spiritual values in natural resources.